Sustained Ocular Hypertension Induces Dendritic Degeneration of Mouse Retinal Ganglion Cells That Depends on Cell Type and Location - Feng, Liang (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Glaucoma is characterized by retinal ganglion cell (RGC) death and frequently associated with elevated IOP. How RGCs degenerate before death is little understood, so we sought to investigate RGC degeneration in a mouse model of ocular hypertension. METHODS. A laser-induced mouse model of chronic ocular hypertension mimicked human high-tension glaucoma. Immunohistochemistry was used to characterize overall RGC loss and an optomotor behavioral test to measure corresponding changes in visual capacity. Changes in RGC functional properties were characterized by a large-scale multielectrode array (MEA). The transgenic Thy-1-YFP mouse line, in which a small number of RGCs are labeled with yellow fluorescent protein (YFP), permitted investigation of whether subtypes of RGCs or RGCs from particular retinal areas were differentially vulnerable to elevated IOP. RESULTS. Sustained IOP elevation in mice was achieved by laser photocoagulation. We confirmed RGC loss and decreased visual acuity in ocular hypertensive mice. Furthermore, these mice had fewer visually responsive cells with smaller receptive field sizes compared to controls. We demonstrated that RGC dendritic shrinkage started from the vertical axis of hypertensive eyes and that mono-laminated ON cells were more susceptible to IOP elevation than bi-laminated ON-OFF cells. Moreover, a subgroup of ON RGCs labeled by the SMI-32 antibody exhibited significant dendritic atrophy in the superior quadrant of the hypertensive eyes. CONCLUSIONS. RGC degeneration depends on subtype and location in hypertensive eyes. This study introduces a valuable model to investigate how the structural and functional degeneration of RGCs leads to visual impairments.